National Integration Literacy in the Digital Space: A Study of Students at HKBP Nommensen University Pematangsiantar - Dian Tama Lidya Pardede; Wikky Pramudya Jasa; Rahel Nirmalasari Rajagukguk; Daulat Nathanael Banjarnahor (Young Journal of Social Sciences and Humanities, 2026)
This study aims to map digital media consumption patterns and evaluate national integration literacy among students at HKBP Nommensen University Pematangsiantar. Utilizing a quantitative approach with a composite index design, this study involved 32 student respondents from various academic disciplines. Descriptive analysis reveals that the internet has become the primary information infrastructure, with 84.4% of students relying on social media to consume national news (Accessibility Index score of 4.26). Affectively, technology functions as a reinforcement for national values, as evidenced by a exceptionally high Affective Integration Index score (4.38) and high appreciation for ethnic, religious, racial, and intergroup (SARA) diversity (93.8%). However, this study identifies an analytical gap in the Critical Capacity Index (3.92), indicating symptoms of cognitive overconfidence; students feel highly confident in their ability to verify hoaxes, whereas their actual literacy skills remain at a pragmatic-academic stage. This study concludes that higher education institutions must institutionalize critical digital literacy frameworks into curriculum policies to prevent disinformation and cultivate social harmony in the cybersphere.